Corrosion Resistance of β type titanium (TNTZ) in 3%NaCl solution. (August 2019) - Affi, J; Gunawarman,; Yetri, Y; Fajri, H; Juliadmi, D; Nuswantoro, N F; Nurbaiti,; Fonna, S; Tjong, D H; Manjas, M
Abstract: Corrosion resistance of TNTZ in a salted environment has been done using a weight loss method. All samples were immersed in 3% NaCl solution for 2, 4, and 6 weeks. Samples consist of TNTZ (AT), TNTZ (ST), Ti6Al4V ELI, and CP-Ti. The weight of samples was measured before and after the immersion process using digital balance. Microstructure and composition of the sample surfaces were examined by using the optic microscope and EDX, respectively. The lowest corrosion rate after exposure for 6 weeks is CP-Ti while the highest one is TNTZ (AT) that is 0, 003 mmpy. All microstructure of samples shows pitting, and crevice corrosion in the surfaces indicating corrosion has been started to occur on the samples. It was found that the corrosion is due to the destruction of the oxide layer in some weak point as a result of chemical reaction between the metal ions with Cl-ions. Some oxides are formed in the surface of titanium as indicated by a significant increment of oxygen content is the corrosive sample surface. This study indicates the corrosion resistance of TNTZ (ST) (β type Titanium) is much better than other materials in this research.